Analisis Performa Jaringan Local Area Network Dengan Menggunakan Metode Quality Of Service - Arvansyah, M Afdhol; Iwan Iskandar; Teddie Darmizal; Novriyanto, Novriyanto; Pizaini, Pizaini (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
The LAN network center of RSUD Arifin Achmad Pekanbaru is located in the EDP (Electrical Data Processing) building, from where the network is distributed to other buildings within RSUD Arifin Achmad Pekanbaru for data transfer. A common issue that arises is delays in sending and receiving data from computer users in other buildings, causing disruptions in the data reception process. To address this problem, a network performance analysis is necessary to assess the quality of both internet and intranet connections within the RSUD Arifin Achmad Pekanbaru LAN. Therefore, a research study was conducted to measure network performance using the Quality of Service (QoS) method. The objective of this study was to analyze and evaluate the quality of internet and intranet performance in the RSUD Arifin Achmad Pekanbaru LAN. The research findings for internet performance indicate that live streaming on YouTube (720p), downloading a 250MB file, uploading a 250MB file, and accessing national and international websites all fall into the “Excellent” category. Based on the TIPHON standard, the LAN internet network at RSUD Arifin Achmad Pekanbaru is considered very good. Regarding intranet performance, the average throughput is 27,835.666Kbps, with zero packet loss, placing it in the “Excellent” category. The average delay is 374.614ms, categorized as “Moderate,” and the average jitter is 11.46066937ms, categorized as “Good” according to the TIPHON standard